2012
DOI: 10.1177/1470320312456579
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into mild electric foot shock stress-induced cognitive enhancement: possible role of angiotensin neuropeptides

Abstract: This study was designed to investigate the role of angiotensin neuropeptides in mild electric foot shock stress-induced cognitive enhancement in mice. Mild stress was induced by applying mild electric foot shocks of 0.15 mA intensity for 0.5 s. The stress-induced alteration in cognition was assessed using a Morris water maze test. The animals were subjected to mild electric foot shocks 5 min before we recorded escape latency time (ELT), an index of learning, during the first 4 days of a 5-day trial in the Morr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In the present study, restraint and cold stress not only augmented corticosterone levels, blood glucose levels and biomarkers of oxidative stress, but also diminished the glutathione antioxidant defense system in the liver tissues. Our results corroborate other studies that reported an increase of corticosterone levels under several stress models such as restraint and cold, immobilization and cold, besides other models of stress induction [ 2 , 4 6 , 20 , 29 ]. Besides that, we showed a decreased of the corticosterone level associated with RJ supplementation, even in absence of stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, restraint and cold stress not only augmented corticosterone levels, blood glucose levels and biomarkers of oxidative stress, but also diminished the glutathione antioxidant defense system in the liver tissues. Our results corroborate other studies that reported an increase of corticosterone levels under several stress models such as restraint and cold, immobilization and cold, besides other models of stress induction [ 2 , 4 6 , 20 , 29 ]. Besides that, we showed a decreased of the corticosterone level associated with RJ supplementation, even in absence of stress.…”
Section: Discussionsupporting
confidence: 92%
“…Physical and psychological stress activates the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS), increasing plasma glucocorticoid levels [ 3 ]. Increased corticosterone levels were observed in stress responses using the stress models, such as restraint and cold [ 2 ], immobilization [ 4 ], cold [ 5 ], cold water immersion [ 5 ], electric foot shock [ 6 ] and social isolation stress [ 7 ]. Corticosterone increases gluconeogenesis and hepatic glycogenolysis in rats, resulting in an increase in the availability of metabolic substrates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Our own studies have described the dual role of angiotensin neuropeptides in cognition. 8,135 There have been contradictory results, i.e. both pain attenuation and increased pain sensitivity with RAS blockers.…”
Section: Possible Hypothesis For Dual Actions Of the Rasmentioning
confidence: 99%
“…5,7,8 Studies based on pharmacological antagonism of RAS have mainly described the stress-inducing role of angiotensin. 9,132 On the other hand, studies employing TGR(ASrAOGEN)680, within an active central angiotensin system, have shown the stress-attenuating role of endogenous angiotensin.…”
Section: Possible Hypothesis For Dual Actions Of the Rasmentioning
confidence: 99%
See 1 more Smart Citation